The effectiveness of various gargle formulations and salt water against SARS-CoV-2 - Vunjia Tiong; Pouya Hassandarvish; Sazaly Abu Bakar; Nizam Bin Baharom; Farishah Nur Abdul Samad; Che Ilina Binti Che Isahak; Nurul Azmawati Mohamed @ Abd Aziz; Wan Shahida Wan Sulaiman (Nature Publishing Group, 2024)
Indexed by WOS/SCOPUS/ERA